PRAKTIK KEWIRAUSAHAAN GEREJA - Mika Daddu Ngedi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
This study aims to examine and describe the entrepreneurial practices of the Pentecostal church in alleviating poverty in Wamena. The method in this research is an explanatory sequential mixed method. It first conducts quantitative research, analyzes the results, and then arranges the results to explain them in more details with qualitative research. The sample is GPdI Elshaddai Wamena and GPdI Elroi Wamena purposively selected the congregations that did entrepreneurship practices. Data collection techniques are through questionnaires, observation, and interviews. Data is collected and analyzed quantitatively, through the relative frequency distribution table, and described qualitatively. The results showed 132 GPdI Elshaddai Wamena congregations and 156 GPdI Elroi Wamena congregations had practiced entrepreneurship in the church well. Entrepreneurship practices carried out by GPdI Elshaddai Wamena and GPdI Elroi Wamena have contributed to alleviating poverty in Wamena.